Maisyah and Culture of Work as Motivation for Work, Analysis in the General Elections Commission Secretariat (KPU) Musi Rawas Regency - Supriadi Supriadi; Pasiska Pasiska (El-Ghiroh : Jurnal Studi Keislaman, 2020)
This study aims to determine the effect of Maisyah and Culture of Work toward the Work Motivation Employee of General Elections Commissionof Musi Rawas regency. This study involved 4 respondents, all of which were employees of General Elections Commissionof Musi Rawas regency. To collect the data, this study used a set of questionnaires and the respond given by the sample was analyzed by (1) average score, (2) multiple linearity regression, (3)determination coefficient, (4) partial t-test and F test techniques.Based on the result analysis, it was found out that (1) there is a positive correlation between independent variables with the dependent variables, (2) the magnitude of independent variables influence toward the dependent variable was 40.40% and (3) the partial t – test and F – test result showed higher coefficient values than those on the critical value of the t and F tables. Based on these findings, it was concluded that maisyah and culture of work, separately and simultaneously, influenced the work motivation employee of General Elections Commission of Musi Rawas regency.